Mucin-type O-glycosylation in gastric carcinogenesis - Duarte, HO (2016)
Mucin-type O-glycosylation plays a crucial role in several physiological and pathological processes of the gastric tissue. Modifications in enzymes responsible for key glycosylation steps and the consequent abnormal biosynthesis and expression of their glycan products constitute well-established molecular hallmarks of disease state. This review addresses the major role played by mucins and associated O-glycan structures in Helicobacter pylori adhesion to the gastric mucosa and the subsequent establishment of a chronic infection, with concomitant drastic alterations of the gastric epithelium glycophenotype. Furthermore, alterations of mucin expression pattern and glycan signatures occurring in preneoplastic lesions and in gastric carcinoma are also described, as well as their impact throughout the gastric carcinogenesis cascade and in cancer progression. Altogether, mucin-type O-glycosylation alterations may represent promising biomarkers with potential screening and prognostic applications, as well as predictors of cancer patients’ response to therapy.